2021
DOI: 10.1002/ppul.25695
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the environmental factors related to the decrease in Pediatric Emergency Department referrals for acute asthma during the SARS‐CoV‐2 pandemic

Abstract: Background: Lockdown measures during the SARS-CoV-2 pandemic determined radical changes to behavioral and social habits, that were reflected by a reduction in the transmission of respiratory pathogens and in anthropogenic atmospheric emissions.Objective: This ecological study aims to provide a descriptive evaluation on how restrictive measures during the SARS-CoV-2 pandemic impacted Pediatric Emergency Department (PED) referrals for asthma exacerbations, and their potentially associated environmental triggers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…They found that this was due to the closing of day care and schools, less air pollution because of reduced travel and fear of visiting hospitals during the peak of the pandemic that in turn led to avoidance or delay in seeking medical care. They also attributed this observation to reduced exposure to viruses; however, they did not evaluate viral triggers in their study 13 . We found that during the peak period in 2021, respiratory viruses were the most frequent trigger for SAA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They found that this was due to the closing of day care and schools, less air pollution because of reduced travel and fear of visiting hospitals during the peak of the pandemic that in turn led to avoidance or delay in seeking medical care. They also attributed this observation to reduced exposure to viruses; however, they did not evaluate viral triggers in their study 13 . We found that during the peak period in 2021, respiratory viruses were the most frequent trigger for SAA.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that the societal changes during the COVID-19 pandemic, in terms of the environment, medical practice and medication usage, have significantly influenced asthma management and outcomes 12 . While the incidence of asthma exacerbations in children during the COVID-19 pandemic has been evaluated 11,[13][14][15] , the incidence of SAA requiring PICU admission and treatment during the pandemic is, to our knowledge, not known. Therefore, the aim of this study was to examine the trend of admissions for SAA at the PICU before and during the COVID-19 pandemic and to evaluate whether this could be linked to the COVID-19 restrictions or other external factors including environmental triggers.…”
Section: Introductionmentioning
confidence: 99%
“…A study on asthmatic children in Kobe showed a significant positive correlation between the ED visits volumes and SO 2 levels, and the SO 2 levels has dropped significantly after Japan declared a state of COVID-19 emergency [ 22 ]. During the lockdown in the USA, the concentration of traffic pollutant NO 2 decreased by 46% and C 6 H 6 decreased by 53% [ 23 ]. After the implementation of prevention and control measures such as Philadelphia Home Order, the positive rate of rhinovirus detection declined significantly [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when the restrictions were lifted, there were increased visits during the fall but SO 2 levels remained low, raising the possibility for other driving factors [49]. In Europe, there was an observed decline both pollutant levels and ED visits [50,53] and hospitalizations due asthma exacerbations [54]. Conversely, Sayed et al [55] reported a reduction in pediatric asthma-related healthcare visits but not observe changes in air pollutant levels of PM 2.5 , PM 10 , O 3 and NO 2 during that time period when compared with previous historic trends.…”
Section: Impact Of Coronavirus Disease 2019mentioning
confidence: 99%